Bulletin hispanique. . Annales de la Faculté des Lettres de Bordeaux et des Universités du Midi
= Annales de la Faculté des Lettres de Bordeaux et des Universités du Midi, 27(1905)-30(1908);32(1910)-33(1911);52(1930);59(1937)-60(1938).